Acute Toxicity and Antipyretic Test of Ethanol Extract of Sterculia Quadrifida. R. Br. Leaves as Traditional Medicine - Fernandez, Stefany S.A; Mbunga, Dominus; Amaral, Acacio Cardoso; Lau, Lidia; Feoh, Putriasa G (JURNAL INFO KESEHATAN, 2023)
Sterculia quadrifida (SQ) is a plant which is also known as "faloak" by the people of East Nusa Tenggara. The secondary metabolite content of this plant has sufficient potential to be developed. Taking the bark of SQ which is not balanced with its preservation can threaten its survival. The use of SQ leaves as a new traditional medicine needs to be tested for its efficacy and safety.The aim of the study was to provide information about the efficacy and safety of SQ leaves in the development of new traditional medicines. The acute toxicity test used the fix-dose combination method according to the BPOM recommendation. A single oral dose of 2000 mg/KgBw of extract was given to five male mice at 24 h intervals. Animals were observed individually for any clinical signs of toxicity or mortality for 24 hours and 14 days. DPT (difteri, pertussis, tetanus)-Hb (Hepatitis-B) was used as a fever inducer in the antipyretic test of infusion and ethanol extract of SQ leaves. For acute treatment, the ethanol extract of Sterculia quadrifida (EESQ)  did not reveal any signs of toxicity or mortality in any animal, during the observation period. The LD50 of extract was estimated to be greater than 2000 mg/KgBw. A dose of 2000 mg/KgBw  in mice for 14 days showed significant side effects on the liver and spleen which were marked by organ weights that were significantly different from the control group. Paracetamol as positive control, infusion of Sterculia quadrifida leaves (ISQ) 100%, and EESQ 400 mg/KgBw showed a significant difference (p<0.05) with the negative control group. The results showed that SQ leaf has potential as an antipyretic, but liver function must be monitored, even though the LD50 value is above 2000 mg/KgBw.